ANALISIS YURIDIS PELAKSANAAN PUTUSAN SENGKETA TUMPANG TINDIH TANAH SENDANGMULYO KOTA SEMARANG - Muhammad Romy; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
The need for land is an important aspect of people's lives in defending their land in order to create an orderly, safe and peaceful life. The state regulates the interests of land for the community in accordance with the law in order to achieve the welfare of the people based on the law. In the process there can be conflicts of interest, disputes, disputes that need to be handled wisely until they need to be resolved through court decisions. In fact, this is not implemented properly which has an impact on the parties concerned. The purposes of this study are (1) to determine the form of execution of court decisions in land overlapping disputes, Sendangmulyo Village, Semarang City (2) to determine the legal consequences that arise for the parties from the act of denying court decisions in the execution of these decisions. This study uses a qualitative descriptive research method with an empirical juridical approach. The results of the study show that (1) the form of execution of decisions in land overlapping disputes in Sendangmulyo Village, Semarang City because the Semarang City Land Office does not follow up in the form of revocation of the disputed object that is required as stated in the verdict (2) The legal consequences of the act of denying the court's decision In the execution of the decision, the Semarang City Land Office may be subject to administrative sanctions for abusing their authority and taking actions that are contrary to the court's decision.